Where is the missing chicken bone ? a case of foreign body bronchiectasis. - Haroon, Raihanah; Ahmad, Nur Fathihah; Zainal, Nur Farhanah (2021)
INTRODUCTION: Foreign body aspiration is an uncommon cause of bronchiectasis in adults. While an obstructive foreign body is readily identified following clinical history of aspiration, there are reports in literature where the dislodged foreign body is neglected by fully conscious adults. Prolonged endobronchial retention of foreign body will eventually lead to recurrent infection and subsequent bronchiectasis. REPORT: Here we describe a patient with a retained chicken bone for 10 years who presented with worsening symptoms of bronchiectasis for 1 month. A chicken bone was discovered in the right lower lobe bronchus along with localized cystic bronchiectasis at the middle and lower lobes as well as superimposed lung infection. CONCLUSION: Patient was subsequently subjected for removal of foreign body using rigid bronchoscopy